Comparison of catalytic activity of CuO nanowires and metallic Cu based on ethanol sensing - Ong, Huiling (2015)
With the development of various renewable energy sources, fuel cell such as direct ethanol fuel cell (DEFC) has started to gain increased attention. However, due to the high cost of platinum and the low ethanol oxidation efficiency, there is a need to search for new material. Copper (Cu) and copper (II) oxide (CuO) nanowires have shown good catalytic activity in several applications such as gas sensor, glucose sensor, anode in fuel cells etc. However, the study of these materials in DEFC has yet been carried out despite the low cost and good sensitivity. Hence, in this project, CuO nanowires and metallic Cu are used as the electrocatalysts to compare their catalytic activity in sensing ethanol solution so as to determine the effectiveness of using nanomaterials in improving the sensitivity of the electrocatalyst. Thermal oxidation method is employed to fabricate CuO nanowires at 500°C in 5 different oxidation times. SEM is used to characterize these nanowires to determine the relationship between different time and morphology of the nanowires. XRD is also used to determine the compound composition and phase identification for the samples. Results show that 5hours is the optimum time for achieving the highest composition of dense and unidirectional CuO nanowires. Both CuO nanowires and metallic Cu undergo cyclic voltammetry (CV) to determine which has the higher catalytic activity in sensing ethanol. It is observed that current peaks for CuO nanowires are much higher than that of metallic Cu, thereby indicating that it has higher catalytic activity as it has oxidised ethanol more efficiently. From the CV graphs obtained, it shows that CuO has the possibility to oxidise ethanol to acetaldehyde, acetic acid and a small amount of carbon dioxide while Cu can most probably trigger the production of acetaldehyde and acetic acid. In addition, 7 different ethanol and sodium hydroxide (NaOH) concentrations are tested to further determine the effect of increasing the concentration and pH of electrolyte on the sensitivity of CuO nanowires and Cu. It shows that the current peaks for both electrocatalysts increase with the concentration of ethanol and sodium hydroxide significantly before saturation occur. Indeed, the increase in the current peak for CuO nanowires is much higher than that of Cu.